Virtuous partisanship: Mary Astell and Catharine Macaulay - Bol, G (2022)
Critics of partisanship argue that partisans lack independence of thought, and that their righteousness and zeal pose a threat to compromise, deliberation, civility and reasonableness. These very contemporary concerns about partisanship echo eighteenth-century complaints in Britain, where worries about partisans’ independence, righteousness and zeal were rife. This is therefore a fruitful period to turn to for insights into virtuous partisanship. Historians of early modern political thought on party and partisanship have exclusively turned to canonical men, however, who are primarily concerned with harmony and unity. By contrast, I explore the political thought and lives of two eighteenth-century English female political thinkers and partisans, Mary Astell (1666–1731) and Catharine Macaulay (1731–1791). Whilst they were excluded from formal institutions of politics, they were to some extent also politically included, in that they were involved partisans who belonged to a political group and contributed to political debates.